Impact of knowledge management and intellectual capital on organizational performance in construction SME - Sucena, A.; Matos, F.; Nunes, A. (Journal of Law and Sustainable Development, 2024)
Objective: This paper explores the relationship between intellectual capital and knowledge management in construction companies and how they impact organisational performance. Theoretical Framework: The construction industry is characterized by a unique set of challenges related to knowledge management and intellectual capital. Project-based work is a dominant feature, necessitating robust knowledge sharing among stakeholders. Method: This article employs a statistical approach to examine the variables under investigation through a Structural Equation Modelling (SEM). The hypothesis proposed was tested using this methodology. Data were collected via a questionnaire administered to 88 individuals occupying managerial roles in small and medium-sized enterprises (SMEs) operating within the construction industry. Results and Discussion: The study concludes that intellectual capital and knowledge management have a significant positive impact on the performance of construction companies and recommends that these concepts be integrated into the management practices of construction companies. Research Implications: Correct combination by companies in the construction sector of the constructs intellectual capital and knowledge management can create dynamics that significantly improve the performance of the organisations from the construction sector. Originality/Value: Construction companies, like any other businesses, can benefit from effective knowledge management and the efficient use of intellectual capital to increase their competitiveness and long-term success.